Tensions in talent: A micro practice perspective on the implementation of high potential talent development programs in multinational corporations. Issue 2 (2nd November 2020) - Garavan, Thomas N.; Morley, Michael J.; Cross, Christine; Carbery, Ronan; Darcy, Colette
Abstract: Drawing on the utility of paradox theory and adopting a micro‐practice perspective, we explore the implementation of high potential talent development (HiPo) programs in multinational corporations (MNCs). In doing so we take an emergent approach to implementation and seek to cast light on some of the day‐to‐day tensions that arise, along with key responses that salient actors appear to make when navigating these paradoxes. Through an inductive, mixed method study involving nine MNCs, we found that, over time, actors construed three particular sets of performance paradoxes relating to variations in their goals, in their beliefs, and in their roles in the particular HiPo programs in focus. We also found that these actors responded to the tensions experienced using an assortment of both defensive and proactive actions. Finally, we uncovered that both the tensions and responses in play vary with the implementation phase of the HiPo program. We highlight some key practice implications that arise from our work, acknowledge attendant limitations and identify possible directions for future research.